Paweł Brzostowski (1739–1827). Twórca Rzeczpospolitej Pawłowskiej - Skodlarski, Janusz (Annales. Etyka w Życiu Gospodarczym, 2009)
Those who have written on Paweł Brzostowski have lacked to pay much attention to his patriotism and his activities as a priest. Some have disapproved the fact that in hard times he left his peasants and sought peace abroad. It is obvious that he lacked the courage of priest Stanisław Brzóska or one of priest Ignacy Skorupka to take the leadership of his own army of peasants to defend Poland. Yet he showed through his life much commitment to strengthen Poland in order to avoid its defeat. He never stooped to the role of tsar’s confidant like other magnates and priests. His peasant army participated in the Kościuszko Insurrection and the November Insurrection. In 1798, after Napoleon’s army had entered Italy, he returned to Poland and gave away 3 000 Zlotys aid to peasants. He also made sure that the fund for the teacher, the doctor and the chemist’s always served the local community. J. Bartyś states that Paweł Brzostowski was a priest by choice: “he always strived to put into practice the Church’s teaching on neighbour-love, honesty and equality of all people regardless their social status”.